Development of thermal insulating lightweight foamed concrete reinforced with polypropylene fibres - Ahmed Jhatial, Ashfaque; Goh, Wan Inn; Mohamad, Noridah; Ali Rind, Touqeer; Sandhu, Abdul Razzaque (Springer, 2020)
The construction of concentrated infrastructures due to rapid urbanization has given rise to urban heat island (UHI) phenomenon which causes temperature of urban areas to significantly increase compared to its adjacent cooler rural areas. The absorption of heat in the form of solar radiation by infrastructures is the main contributor to UHI, which results in the rise in the ambient temperature at night. This has forced the construction industry to focus on thermal insulating building materials such as foamed concrete. Air voids in the matrix of foamed concrete allow it to reduce the thermal conductivity and dry density; however, due to its reduced density, foamed concrete is prone to microcracking which results in loss of strength. To counteract the development and propagation of microcracks, polypropylene (PP) fibres are used to reinforce the foamed concrete. Therefore, in this study, foamed concrete of density 1600 kg/m3 was reinforced using PP fibres in three percentages, 0.20%, 0.25% and 0.30%. Thermal performance, in terms of thermal conductivity and surface temperature, was conducted as well as the compressive and tensile strength was determined. It was observed that the PP fibres not only enhanced the strength but also significantly lowered the thermal conductivity and absorbed less heat.